Dextran Administration Associated with Large Volume Paracentesis Management of Patients with Cirrhosis and Ascites - S. KAPICIOĞLU; A. BAKİ and O. YEŞİLDAĞ and N. KAYA and H. KAHRAMAN and M. ESER (Turkish Journal of Gastroenterology, 2020)
-